Okinawanos e não-okinawanos em Campo Grande: relações de parentesco e famílias - Kubota, Nádia Fujiko Luna (2015)
Japan has been permeated by the myth of ethnic homogeneity. The idea that homogeneity is present even in countries receiving "nikkeys" immigrants, as is the case in Brazil. However, a few decades it has been possible to note that the multiplicity and diversity are also part of the japanese reality. This diversity makes the group think of themselves and others to think as opposites. Thus, Campo Grande becomes field investigation of this heterogeneity, since it possesses two distinct groups - Okinawans and "naichi" (japanese) - in an opposition movement and aggregation throughout history. When thinking of a "Japanese unit" is over for not paying attention to details that make up the relations between the groups involved (Okinawans, non-Okinawans and non-western). The purpose of this research is therefore to understand how notions of family and belonging can build the oppositions and differences between Japanese immigrants and their descendants.